1985
DOI: 10.1071/ea9850082
|View full text |Cite
|
Sign up to set email alerts
|

Performance of North American and Australian lucernes in the Queensland subtropics 2. Yield and plant survival in irrigated stands

Abstract: The yield and plant survival of 23 North American and 5 Australian lucerne lines were assessed at Biloela and Gatton, Queensland, under irrigation over a 40-month period. Total yields ranged from 49 to 72 t/ha at Biloela and from 14 to 47 t/ha at Gatton. The relative performances of lines were similar at each site. The highly winter non-dormant lines were the highest yielding, particularly HS Gen 3 Composite, Matador and CUF 10 1. Semi-dormant lines were generally more productive than nondormant and dormant li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These yields are consistent with those from other temperate and subtropical areas of the world. In Australia, for example, annual yields obtained under cutting experiments ranged from 14.7 to 21.6 t DM ha À1 yr À1 in subtropical Queensland environments (Lowe, Gramshaw, Bowdler, & Ludke, 1985) and between 5.2 and 19.9 t DM ha À1 yr À1 under temperate Tasmanian environments (Pembleton, Donaghy, Volenec, Smith, & Rawnsley, 2010). In Lincoln, New Zealand, data from grazing trials indicated annual yields from 10 t DM ha À1 to 21 t DM ha À1 yr À1 under rainfed (Mills et al, 2015) and irrigated (Brown & Moot, 2004) conditions, respectively.…”
Section: Yield Gap Estimationmentioning
confidence: 99%
“…These yields are consistent with those from other temperate and subtropical areas of the world. In Australia, for example, annual yields obtained under cutting experiments ranged from 14.7 to 21.6 t DM ha À1 yr À1 in subtropical Queensland environments (Lowe, Gramshaw, Bowdler, & Ludke, 1985) and between 5.2 and 19.9 t DM ha À1 yr À1 under temperate Tasmanian environments (Pembleton, Donaghy, Volenec, Smith, & Rawnsley, 2010). In Lincoln, New Zealand, data from grazing trials indicated annual yields from 10 t DM ha À1 to 21 t DM ha À1 yr À1 under rainfed (Mills et al, 2015) and irrigated (Brown & Moot, 2004) conditions, respectively.…”
Section: Yield Gap Estimationmentioning
confidence: 99%
“…Generally, it was shown that there was a wide range in the dry matter production of these imported cultivars under Australian conditions. Winter-active cultivars produced higher yields than semi-dormant and dormant cultivars but were less persistent (in NSW, Rogers 1981;Lodge 1985Lodge , 1986in Queensland, Gramshaw et al 1985;Lloyd et al 1985;Lowe et al 1985a). The superior imported cultivars became significant in commercial sowings before the release of elite Australian-bred cultivars.…”
Section: Breeding Objectives Post 1972mentioning
confidence: 99%
“…In understanding the hitherto unknown basis for the performance of these new lines in Queensland and NSW, it was found that lucerne yield was correlated with winter activity level and persistence. Persistence was directly related to disease resistance and initial stand density (Lowe et al 1985a(Lowe et al , 1987. It was established that different defoliation systems were needed to manage cultivars from different dormancy classes and these differed from those previously utilised for Hunter River (Lowe et al 1985b;Lodge 1986;Gramshaw et al 1993).…”
Section: Breeding Objectives Post 1972mentioning
confidence: 99%
“…Differences in productivity among varieties may be observed under summer and winter conditions, particularly during the earlier stages of regrowth after cutting. High yields of alfalfa have been found to be associated with reduced winter dormancy (SARRAJ 1985) and improved resistance to root rot and anthracnose (LOWE et al 1985) and other pests (MARBLE 1985).…”
Section: Introductionmentioning
confidence: 99%